Peran Buah Naga Untuk Berat Badan Pada Anak-Anak Di Klinik Siti Kholijah Medan - Ivansri Marsaulina; Endryani Syafitri; Muthia Sari Mardha; Ade Ilma ilham (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
Overweight and obesity were serious health problems and were sufficiently calculated because they could increase morbidity and mortality in the long term. Red dragon fruit was a fruit that contained antioxidants and high fiber. Red dragon fruit also contained niacin, ascorbic acid, and palmitic acid which were believed to increase HDL levels and reduce LDL levels. PurposeTo know the effect of giving red dragon on LDL and HDL levels in obese female students of the undergraduate nutrition study program at Klinik Siti Kholijah Medan. The average levels of LDL before the intervention were 125,90 mg/dl and after the intervention were 107,90 mg/dl. Meanwhile, The average levels of HDL before intervention were 53,10 mg/dl and 58,30 mg/dl after the intervention. The result of the paired t-test on the LDL levels showed the p-value 0,002 (p<0,05). The result of the paired t-test on the HDL levels showed the p-value 0,001 (p<0,05). Results 12,2% of children were picky eaters and 1,4% of children were severe malnourished. There was no difference in nutritional status and food intake between picky eaters and non-picky eaters children (p>0.05). Conclusion: There was an effect of giving red dragon fruit (Hylocereus polyrhizus) on LDL and HDL levels in obese female students of bacheler of midwifery studiens at helvetia health institute Medan At the siti kholijah cklinik in medan